Brexit and the working class on Teesside: Moving beyond reductionism. (December 2020) - Telford, Luke; Wistow, Jonathan
Too often, members of the working class who voted to leave the European Union in the 2016 referendum have been framed as uneducated and unaware of their own economic interests. This article, based on 26 in-depth face-to-face interviews and a further telephone interview on Teesside in the North East of England, offers an alternative perspective that is more nuanced and less reductionist. The article critiques some of the commonly heard tropes regarding the rationale for voting leave, it then exposes how leave voters rooted their decision in a localised experience of neoliberalism's slow-motion social dislocation linked to the deindustrialisation of the area and the failure of political parties, particularly the Labour Party, to speak for regional or working-class interests.